Conceptual design of a fixture-based reconfigurable spot welding system - Sequeira, Michael Allan (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2009.